PENINGKATAN KEMAMPUAN MENYUSUN KALIMAT EFEKTIF MELALUI TEKNIK MENYUSUN UNSUR KALIMAT PADA SISWA KELAS XI SMA - Suprapti (Sasando, 2020)
The purpose of this study is (1) obtaining an objective description of the increase in the ability of students of the XI-SMA class in composing effective sentences after the student has been given a provision to compose the sentence element and (2) obtained an objective description of the change in student behaviour during the study.  , one way that can be pursued is by increasing the ability to compose effective sentences. The results showed that there was an increase in the ability to compose effective sentences through the technique of arranging the elements of the sentence appears in the results of pretes on composing elements of sentences obtained by the students with an average score of class 5.85, while the results of pretes on the ability to compose effective sentences with the average score of class reaches 6.35. The test results on the sentence element in cycle I reached an average score of 6.58 which means an increase of 0.73 or 1.83%, while the test results on the effective sentence on the I cycle achieved an average score of 7.59 which means an increase of 0.91 or 2.28%, while the test result on effective sentences in cycle II was obtained an average score of 8.01 which means an increase of 0.42 or 1.05% Keywords: increased ability, compose effective sentences, techniques for composing sentence elements.